Analysis of the Impact of the Conic Aperture in the Differentially Pumped Chamber (Advances in Military Technology, 2019)
The paper focuses on the simulation of medium dynamics in the environmental scanning electron microscope. In particular, the paper examines the conical aperture location effect in the differentially pumped chamber and the width of the pumping channel in this chamber. The solution is based on the Taylor-Maccoll theory about the impact of the shock wave and was obtained by the use of continuum and finite volume methods in the ANSYS Fluent system.
Keywords: ANSYS Fluent; differentially pumped chamber; environmental scanning electron microscope (ESEM); finite volume method; Taylor-Maccoll theory